IMPACT OF AGRICULTURAL VALUE CHAINS ON RURAL ECONOMIC DEVELOPMENT IN ENUGU STATE (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
The value chains involve production, processing and marketing of agricultural products, which play a crucial role in rural economic development by increasing income, employment and food security. This paper analyzes their role within the Enugu State, in Nigeria, which is an agrarian area and a rural poor region. The study uses the secondary data sources such as national surveys and policy reportage and scholarly literature, 1980-2025, to analyze the role played by value chains of crops such as cassava, yam, and poultry in rural livelihoods. Results show that integrated value chains raise rural incomes between 30 and 40 percent and generate more than 50000 jobs each year in Enugu, but poor infrastructure and market access remain a problem. The analysis fills the gaps in the state-specific research combining the data of the past and present and providing information about gender relations and innovative technologies. Stronger cooperatives, better of roads in rural areas, and the encouragement of agro-processing hubs are among the recommendations to help increase the efficiency of the value chain. The strategies can be used to promote inclusive rural development in Enugu State, which would decrease poverty and increase economic resilience.